2014
DOI: 10.1177/1470320314530018
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with aliskiren versus ramipril or losartan added to conventional therapy in patients with type 2 diabetes mellitus, uncontrolled hypertension and microalbuminuria

Abstract: Hypothesis/Introduction: The aim of this study was to assess the antihypertensive efficacy and safety of aliskiren versus ramipril or losartan in hypertensive patients with type 2 diabetes mellitus, microalbuminuria and uncontrolled hypertension, despite the use of optimal conventional antihypertensive therapy. Materials and methods: In this open-label active comparator study, 126 patients were randomly assigned to receive 24 weeks of additional therapy with aliskiren (Group A) or either losartan or ramipril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At home, she was taking the following drugs: olmesartan/hydrochlorothiazide, methylprednisolone (recently suspended), pantoprazole, epoetin alfa and cholecalciferol. [37][38][39][40][41][42][43][44][45][46][47] We performed an echocardiogram that showed normal kinesis and function of LV (EF 60%), left atrium dilation (21 cm 2 ), moderate mitral and mild tricuspid regurgitation (Fig. 1A).…”
Section: Case Reportmentioning
confidence: 99%
“…At home, she was taking the following drugs: olmesartan/hydrochlorothiazide, methylprednisolone (recently suspended), pantoprazole, epoetin alfa and cholecalciferol. [37][38][39][40][41][42][43][44][45][46][47] We performed an echocardiogram that showed normal kinesis and function of LV (EF 60%), left atrium dilation (21 cm 2 ), moderate mitral and mild tricuspid regurgitation (Fig. 1A).…”
Section: Case Reportmentioning
confidence: 99%
“…The addition of ALI 300 mg in the VAL/HCTZ 160/25 mg regimen in diabetic individuals showed greater BP reductions, however this did not achieve statistical significance [60]. In a recent randomized control trial by Imbalzano et al, ALI addition to optimal antihypertensive therapy showed higher BP and microalbuminuria reductions than LOS or RAM addition in patients with uncontrolled BP and DM [79]. …”
Section: Aliskiren and Blood Pressure Loweringmentioning
confidence: 99%
“…DRI also showed a significant reduction in microalbuminuria as compared to CCB/ARB after a period of six months. Hence, the addition of aliskiren to regular hypertensive drugs can be highly effective in reducing the blood pressure and urinary albumin excretion [ 53 - 57 ].…”
Section: Reviewmentioning
confidence: 99%